Differential transferrin expression in placentae from normal and abnormal pregnancies: a pilot study - Kralova, Alena; Svetlikova, Marta; Madar, Jindrich; Ulcova-Gallova, Zdena; Bukovsky, Antonin; Peknicova, Jana (Reproductive biology and endocrinology, 2008)
BACKGROUND: The placenta is an important site for iron metabolism in humans. It transfers iron from the mother to the fetus. One of the major iron transport proteins is transferrin, which is a blood plasma protein crucial for iron uptake. Its localization and expression may be one of the markers to distinguish placental dysfunction. METHODS: In the experimental study we used antibody preparation, mass spectrometric analysis, biochemical and immunocytochemical methods for characterization of transferrin expression on the human choriocarcinoma cell line JAR (JAR cells), placental lysates, and cryostat sections. Newly designed monoclonal antibody TRO-tf-01 to human transferrin was applied on human placentae from normal (n = 3) and abnormal (n = 9) pregnancies. RESULTS: Variations of transferrin expression were detected in villous syncytiotrophoblast, which is in direct contact with maternal blood. In placentae from normal pregnancies, the expression of transferrin in the syncytium was significantly lower (p < 0.001) when compared to placentae from abnormal ones (gestational diabetes, pregnancy induced hypertension, drug abuse). CONCLUSION: These observations suggest that in the case of abnormal pregnancies, the fetus may require higher levels of transferrin in order to prevent iron depletion due to the stress from the placental dysfunction.
Keywords: Pregnancy Complications; komplikace těhotenství; těhotenství; imunohistochemie; Stress, Physiological; monoklonální protilátky; mužské pohlaví; placenta; Antibodies, Monoclonal; železo; Adult; Placenta; fyziologický stres; Transferrin; transferin; Models, Biological; Immunohistochemistry; Iron; ženské pohlaví; Placenta Diseases; Humans; Pregnancy; pilotní projekty; biologické modely; Pilot Projects; dospělí; nemoci placenty; Female; Epitopes; lidé; Male; epitopy